Pemafaatan Strategic Cost Management Dengan Metode Target Costing Untuk Meningkatkan Efisiensi dan Daya Saing UMKM - Amanda Anggraeni; Sri Rahayu; Abdillah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Amidst increasingly competitive global and national economic dynamics, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a crucial role as a key pillar driving economic growth. However, in their efforts to maintain their business sustainability, MSMEs face various challenges, particularly related to cost efficiency and increasing competitiveness. This study employs a qualitative approach with a library research method, involving data collection through a review of relevant scientific literature. Most studies demonstrate that this method enables MSMEs to reduce production costs without sacrificing product quality and significantly increase profits. Some studies even report profit growth of more than twofold after implementing the method. This study suggests that Strategic Cost Management, particularly through the application of the Target Costing method, plays a crucial role in improving cost efficiency and strengthening the competitiveness of Micro, Small, and Medium Enterprises (MSMEs).